The American future : [videorecording (DVD)] : a history - Schama, Simon (BBC Video ; Warner Home Video, 2009)
After 9/11, after Katrina, Enron and Baghdad, the robustness of American optimism is struggling to reassert itself against the sobering reality of military frustration and domestic anxieties. This is an America grappling with an un-American sense of its own limits. Turning to fascinating moments in American history to understand the present, connecting legendary presences such as Thomas Jefferson, Henry Ford, and others with contemporary soldiers, businessmen, truckers and politicians. The United States, past and present, facing its moment of truth.